Remittances and Human Capital Development in BRICS - Tsaurai, Kunofiwa (EuroEconomica, 2024)
The study investigated the impact of personal remittances on the development of human capital in BRICS (Brazil, Russia, India, China, South Africa) using panel data (1990-2020) analysis methods such as the fully modified ordinary least squares (FMOLS), dynamic ordinary least squares (DOLS) and the fixed effects. Using the same data set and econometric estimation methods, the study also explored if financial development is a channel through which the positive influence of remittances on human capital development is enhanced. In line with Ali et. al. (2023), the study focused on BRICS because of its global dominance in terms of share of gross domestic product in the world economy and its fastest pace in terms of economic growth and development. The influence of remittances on human capital development was found to be positive but insignificant under both the fixed effects and FMOLS, results which generally agrees with literature (positive rationale hypothesis). The dynamic OLS shows that remittances reduced human capital development in a significant manner, consistent with the negative rationale hypothesis. The complementarity between remittances and financial development had a non-significant positive impact on human capital development. The study produced results which show that internet usage (DOLS), government consumption expenditure (FMOLS), trade openness (fixed effects, FMOLS) and economic growth (DOLS, FMOLS) had a significant positive effect on human capital development in BRICS. Policies aimed at increasing internet usage, government consumption on education, trade openness and economic growth must therefore be implemented by the responsible authorities in BRICS to enhance human capital development.